PENGARUH FAKTOR-FAKTOR MANAJERIAL DAN PENGELOLAAN DANA TERHADAP PENGAMBILAN KEPUTUSAN SERTA IMPLIKASINYA PADA KINERJA KEUANGAN PADA KANTOR KESEHATAN PELABUHAN KELAS III KOTA LHOKSEUMAWE - Suriyani; Azhari; Kamaruddin (Business Administration Department, School of Economics and Business, Telkom University, 2024)
This study aims to determine the influence of managerial factors and fund management ondecision-making and its implications for the financial performance of the Port Health Office IIIin Lhokseumawe City. The research method is quantitative with a causal type. The populationand sample in this study consist of 55 employees. The sampling method uses non-probabilitysampling with a saturated sample. Data analysis is performed using path analysis with SPSS.The study results show that the influence of managerial factors on financial performance is42.9%. The influence of fund management on financial performance is 43.8%. The influence ofdecision-making on financial performance is 45.9%. The influence of managerial factors onfund management is 44.1%. The influence of managerial factors on decision-making is 54.7%.The influence of fund management on decision-making is 32.8%. The influence of managerialfactors on financial performance through fund management is 76.8%. The influence of fundmanagement on financial performance through decision-making is 79.8%. The influence ofmanagerial factors on financial performance through decision-making is 74.3%. Thesimultaneous influence of managerial factors, fund management, and decision-making onfinancial performance is 80.6%